(untitled) - Pilling, M. J. (Oxford, 1995)
In classical terms reaction kinetics refers simply to the measurements of rates of reactions. Chemistry is all about reactions, so a knowledge of the rates which they occur is of and practical importance.
Keywords: Chemical kinetics,Động lực học hóa học